Using Mobile Devices for Vocabulary Learning Outside the Classroom: Improving the English as Foreign Language Learners’ Knowledge of High-Frequency Words - Rahmani, Azadeh; Asadi, Vahid; Xodabande, Ismail (Frontiers in Psychology, 2022)
The present study investigated the impacts of mobile assisted vocabulary learning via digital flashcards (DFs). The data were collected from 44 adult English as Foreign Language (EFL) learners in three intact classes in a private language teaching institute in Iran, randomly assigned to experimental (N = 27) and control (N = 17) learning conditions. The experimental group used a freely available DF application (i.e., NGSL builder) to learn items from a recently developed corpus-based word list for high-frequency vocabulary in English (NGSL). The treatment was implemented as out-of-the-classroom learning activities where the EFL learners used DFs to augment their vocabulary knowledge, and their learning gains were compared to the control group that received regular English language education. The participants’ vocabulary knowledge was tested in pre-, post-, and delayed post-tests, and the findings indicated that using DFs for outside the classroom vocabulary learning contributed significantly to short- and long-term improvements in the knowledge of high-frequency words. The study provided empirical evidence for the affordances of mobile assisted vocabulary learning for learning a considerable proportion of core vocabulary and has some implications for addressing the vocabulary learning needs of EFL learners.